Bahan Ajar Digital dalam Pembelajaran di Sekolah Dasar: Analisis Bibliometrik dan Systematic Literature Review - Darmayanti, Mela; Amalia, Ania (SITTAH: Journal of Primary Education, 2024)
In the current technological development era, all sectors of life, including education, are starting to implement technology. One example of technological innovation in education is using digital teaching materials in the learning process. This research aims to determine the use of digital teaching materials in science learning in elementary schools. The research methods used are the Systematic Literature Review (SLR) method and bibliometric analysis. The data used comes from the Google Scholar database. While searching and processing data, researchers used software such as Publish or Perish, Microsoft Excel, Mendeley, Vosviewer, and Covidence. The data used in this research comes from the 75 most relevant articles obtained through various data analysis and extraction stages using Covindence software. Based on research that has been conducted, it was found that research in the field of using digital teaching materials in science learning in elementary schools is fluctuating. The impact of using digital teaching materials in science learning in elementary schools includes increasing social sensitivity, critical thinking skills, 21st-century skills, learning outcomes, and student character.